Early Life Predictors of Socio-Emotional Development in a Sample of Egyptian Infants - Metwally, Ammal M.; Salah El- Din, Ebtissam M.; Shehata, Manal A.; Shaalan, Ashraf; El Etreby, Lobna A.; Kandeel, Wafaa A.; Shaaban, Sanaa Y.; Rabah, Thanaa M. (PloS one, 2016)
Emotional problems are amongst the most critical concerns to be intentionally handled to enhance the wellbeing and development of children. To determine the predictors of socio-emotional development of Egyptian infants related to infant feeding practices, aspects of infant and maternal health and socioeconomic status. A cross-sectional comparative study included 322 breast fed, 240 bottle fed and 93 mixed fed infants, from 6-24 months of age, who were enrolled in the Well-Baby Clinic of the National Research Centre and from pediatric outpatient facilities in urban Cairo. Assessment of socio-emotional development was performed using Bayley Scales of Infant and Toddler Development (Bayley III). Detailed maternal and infant history was recorded. Levels of serum zinc, copper, iron, vitamin B12 and complete blood count (CBC) were assessed in a subsample of 193 infants. The risk of having below average socio-emotional composite score was nearly two and half times among formula-fed infants than among breast-fed infants. By binary logistical regression analysis, predictors of below average socio-emotional score were a lower serum zinc value, being formula fed during the first half-year and introduction of complementary food before the age of six months (p< 0.05). Exclusive breastfeeding and to a lesser extent mixed feeding during the first half year is correlated with above average socio-emotional development. Maternal education and zinc status were also determinants of better infant mental health. Our endeavors ought to be directed towards integrated interventions addressing multiple risks to children's development.